Does El Niño intensity matter for California precipitation?. Issue 2 (19th January 2016) - Hoell, Andrew; Hoerling, Martin; Eischeid, Jon; Wolter, Klaus; Dole, Randall; Perlwitz, Judith; Xu, Taiyi; Cheng, Linyin
Abstract: The sensitivity of California precipitation to El Niño intensity is investigated by applying a multimodel ensemble of historical climate simulations to estimate how November–April precipitation probability distributions vary across three categorizations of El Niño intensity. Weak and moderate El Niño events fail to appreciably alter wet or dry risks across northern and central California, though odds for wet conditions increase across southern California during moderate El Niño. Significant increases in wet probabilities occur during strong El Niño events across the entire state. In California's main northern watershed regions, simulations indicate an 85% chance of greater than normal precipitation and a 50% probability of at least 125% of normal. Our results indicate that both the statewide average and the spatial distribution of California precipitation are sensitive to El Niño intensity. Forecasts of El Niño intensity would thus contribute to improved situational awareness for California water planning and related water resource impacts. Key Points: Strong El Niño greatly increases statewide California wet risk